Dialysis Disequilibrium: Is Acidosis More Important than Urea?. (22nd February 2022) - Athavale, Akshay; Wyburn, Kate R; Snelling, Paul L; Chadban, Steven J
Abstract : Dialysis disequilibrium syndrome is a severe complication associated with dialysis treatment. Manifestations may range from mild such as headache to severe such as seizures and coma. Risk factors for development include initial dialysis treatment, uraemia, metabolic acidosis, and extremes of age. We report a case of dialysis disequilibrium in a patient with a failing kidney transplant secondary to the recurrence of IgA nephropathy. Disturbance in cognition and neurologic functioning occurred six hours after the completion of initiation of intermittent haemodialysis. During two sessions of intermittent haemodialysis of 3 and 4 hours, urea was reduced by 21.9 and 17.2 mmol/L and measured serum osmolality was reduced by 25 and 14 mOsm/kg, respectively. Subsequent admission to the intensive care unit and initiation of continuous renal replacement therapy for 48 hours resulted in complete resolution of symptoms. In this case report, we discuss atypical clinical and radiologic features of dialysis disequilibrium occurring with modest reductions in urea and serum osmolality.